2007
DOI: 10.1016/j.cardiores.2006.11.023
|View full text |Cite
|
Sign up to set email alerts
|

TRPM4, a Ca2+-activated nonselective cation channel in mouse sino-atrial node cells

Abstract: TRPM4 is functionally expressed in SAN cells and may be a key player in the generation and/or perturbation of heart rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(153 citation statements)
references
References 29 publications
5
144
1
Order By: Relevance
“…Thus, excess PIP3, but not excess PIP2, appeared to reverse the attenuated VRAC current in PIP3-or PIP2-depleted cells. We conclude that PIP3 is more directly linked to the activation of VRAC current their effects on PIP3-regulated transporters and channels (4,8), further studies are necessary to clarify to what extent PI3K activation can increase the PIP3 level in intact cardiac cells. As with the relationship between cell swelling and PI3K-related signaling pathways, several reports have shown that mechanical stretch of membrane and cell swelling cause activation of PI3K (16), and the activated PI3K has been suggested to trigger some downstream signaling cascades leading to the activation of VRAC current (5,7,26,33).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, excess PIP3, but not excess PIP2, appeared to reverse the attenuated VRAC current in PIP3-or PIP2-depleted cells. We conclude that PIP3 is more directly linked to the activation of VRAC current their effects on PIP3-regulated transporters and channels (4,8), further studies are necessary to clarify to what extent PI3K activation can increase the PIP3 level in intact cardiac cells. As with the relationship between cell swelling and PI3K-related signaling pathways, several reports have shown that mechanical stretch of membrane and cell swelling cause activation of PI3K (16), and the activated PI3K has been suggested to trigger some downstream signaling cascades leading to the activation of VRAC current (5,7,26,33).…”
Section: Resultsmentioning
confidence: 90%
“…These results are in agreement with the previous studies, in which the effect of these inhibitors on VRAC current was examined in rabbit ventricular cells (5,26), cultured smooth muscle cells (33) and hepatoma cells (11,12 (8), and PIP3 dic8 (Echelon Biosciences) (4) were added to the pipette solution. PIP2 and PIP3 were directly dissolved in the control pipette solution at a concentration of 10 μM (4,8). PIP2-Ab and PIP3-Ab were used at a 1 : 50 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…blood flow, the generation of heart rhythm, and the immune response (33)(34)(35)(36)(37)(38)(39). TRPM4-mediated currents are up-regulated in cardiomyocytes from spontaneous hypertensive rats (40), and gain-of-function mutations in TRPM4 have been associated with familial heart disease (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…A typical trace of an ECG shows the "P-wave", the "P-Q interval" (isoelectric line), the "QRS complex", the "T-wave" and the "U-wave". [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] in the SAN). This "SAN overdrive suppression" on the other elements of the conductive network explains its leading role in driving the pacemaker.…”
Section: Development Of the Human Cardiac Conduction Systemmentioning
confidence: 99%
“…Recently, different transient receptor potential (TRPM) channels have also been described as having a role in this physiological process. TRPM4, a non-selective, calcium-activated cation channel was characterized in the rodent SAN [69] . This sodium and potassium inward current is positively regulated by [Ca 2+ ] i and negatively regulated by ATP.…”
Section: Wwwchinapharcom Weisbrod D Et Almentioning
confidence: 99%